ANALISIS RASIO KEUANGAN SEBAGAI ALAT UNTUK MENILAI KINERJA KEUANGAN PADA PT KARYA LINTAS MANDIRI DI MAKASSAR - Nurhadi Nurhadi (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2016)
As for the author's purpose was to determine whether the financial ratios. Lintas Karya Mandiri can be used as an analytical tool. to assess the financial performance of data collection methods Research Library (Library Research) the research done by reading books reverensi relevant as the basis for determining the basic theory in the discussion. Objectives for the analyzer is generally to determine the level of liquidity, lavarage, activity and protabilitas of a company at PT Karya Lintas Mandiri, while the data collection methods used Research Library (Library Research) the research done by reading books reverensi relevant as the basis for determining the basic theory in the discussion, Fieldwork interview, namely by conducting direct interview to some respondents as staff / employees who are competent in the issues discussed. Documentation, namely the collection of data or documents related to the study material.